IMPROVING THE SECURITY SYSTEM OF CISCO NETWORKS BASED ON SDN TECHNOLOGY - D. T. Xakimbekov; B. M. Ergashev (European Science Publishing, 2025)
This paper explores the integration of Software Defined Networking (SDN) technology into Cisco networks to enhance their security posture. By decoupling the control plane from the data plane, SDN enables centralized network management, dynamic policy enforcement, and granular traffic monitoring. We examine the potential of SDN to detect and mitigate security threats in real-time, offer adaptive responses, and facilitate automation in threat remediation. Various SDN-based security solutions, including Cisco’s own SDN-compatible products, are evaluated in the context of their effectiveness, scalability, and interoperability. This study concludes with a proposed architecture for integrating SDN into Cisco environments to optimize security and operational efficiency.
Keywords: Cisco Networks, Software Defined Networking, Network Security, SDN Security Architecture, Threat Mitigation, Network Automation, Centralized Management, Secure Infrastructure, Policy Enforcement, Cybersecurity.